Hierarchical MFI Zeolites with a Single‐Crystalline Sponge‐Like Mesostructure. Issue 72 (21st November 2018) - Zhang, Yunjuan; Luo, Peng; Xu, Hao; Han, Lu; Wu, Peng; Sun, Huai; Che, Shunai
Abstract: Single‐crystalline sponge‐like MFI mesoporous zeolites (SSMZs) have been synthesized by using bolaform surfactants with an axial chiral binaphthyl core in the hydrophobic tail and triquaternary ammonium head groups, as bifunctional organic structure‐directing agents (OSDAs). By changing the length of alkyl chain between a triquaternary ammonium head group and a binaphthyl group from 4 to 10 carbons, SSMZs with high specific surface area (382–434 m 2  g −1 ), abundant micropore‐mesopore connectivity, and uniform mesopore diameter (4–10 nm) were obtained. OSDAs with an alkyl chain length of 11 and 12 carbons led to the formation of nanorod‐constructed mesoporous MFI zeolites. A geometrical matching between the cylindrical arrangement of the binaphthyl groups and the zeolitic framework is speculated to be the key factor for the formation of mesoporous zeolites. The SSMZ zeolites, with abundant mesopores beneficial for the diffusion of reactants, exhibited significantly higher catalytic efficiencies than those of the conventional ZSM‐5 with a microcrystal morphology (≈1.5 μm). Abstract : Catalytic boost : Single‐crystalline sponge‐like MFI mesoporous zeolites (SSMZs) have been synthesized by using bolaform surfactants with an axial chiral binaphthyl core in the hydrophobic tail and triquaternary ammonium head groups as bifunctional organic structure‐directing agents (OSDAs). The efficiencies for several catalysis reactions have been assessed.